2021
DOI: 10.1002/bsl.2537
|View full text |Cite
|
Sign up to set email alerts
|

DAT1 polymorphism associated with poor decision‐making in males with antisocial personality disorder and high psychopathic traits

Abstract: Studies suggest that abnormalities of the dopaminergic system underlie decision‐making deficits, a hallmark of antisocial personality disorder (ASPD) and psychopathy. The dopamine transporter gene (DAT1) is of particular interest due to a polymorphism that controls dopamine transporter (DAT) activity. However, the association between DAT1 genotypes and decision‐making in ASPD has never been studied. The current study investigated the effect of DAT1 genotype on decision‐making, as measured by the Iowa Gambling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 68 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, the endogenous opioid system has recently been linked to several reward-related antisocial behaviors (e.g., manipulativeness), substance use, and sensation-seeking ( 74 , 75 ), which supports our results regarding Deceitfulness and LPE symptoms. Overall, our results provide evidence of how different neurotransmitter systems may play prominent roles in the emergence of antisocial behaviors ( 14 16 ). Despite that the emphasis in literature is being mainly placed on dopaminergic and serotoninergic systems, the relationship between the opioid system and antisocial behaviors warrants further investigation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Interestingly, the endogenous opioid system has recently been linked to several reward-related antisocial behaviors (e.g., manipulativeness), substance use, and sensation-seeking ( 74 , 75 ), which supports our results regarding Deceitfulness and LPE symptoms. Overall, our results provide evidence of how different neurotransmitter systems may play prominent roles in the emergence of antisocial behaviors ( 14 16 ). Despite that the emphasis in literature is being mainly placed on dopaminergic and serotoninergic systems, the relationship between the opioid system and antisocial behaviors warrants further investigation.…”
Section: Discussionmentioning
confidence: 60%
“…Through a meta-analysis of resting-state connectivity studies in antisocial population, we also showed evidence that both amygdala and mPFC (i.e., ventral and dorsal) exhibited disrupted connectivity ( 12 ). Moreover, there is a growing body of evidence suggesting the importance of serotoninergic [mainly serotonin transporter (5-HTT) and 5-HT 2A and 5-HT 2B receptors] and dopaminergic systems [mainly Dopamine transporter (DAT) and D 2 and D 4 receptors] in our comprehension of antisocial behaviors ( 13 16 ). Indeed, these systems are known to encompass the amygdala/ATL and mPFC (e.g., mesolimbic/mesocortical dopaminergic pathways) ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers believe that the cause of ASPD is a developmental abnormality of the nervous system 43 . Rafiei and Kolla 44 used the Iowa Gambling Task (IGT) and positron emission tomography to confirm abnormalities in the dopaminergic system in ASPD patients. The dopamine transporter gene (DAT1) was related to decision‐making, and ASPD patients with low DAT1 genotype activity performed remarkably worse on the IGT.…”
Section: Discussionmentioning
confidence: 99%
“…The dopamine transporter gene (DAT1) was related to decision‐making, and ASPD patients with low DAT1 genotype activity performed remarkably worse on the IGT. Lower DAT activity was reflected in lower DA reuptake and increased synaptic concentrations of DA 44 . Also, the DAT1 gene interacts with the social environment and drug use to further influence the neural activity of ASPD patients 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation